Origin of Improved Photoelectrochemical Water Splitting in Mixed Perovskite Oxides. Issue 31 (24th September 2018) - Li, Weiwei; Jiang, Kai; Li, Zhongguo; Gong, Shijing; Hoye, Robert L. Z.; Hu, Zhigao; Song, Yinglin; Tian, Chuanmu; Kim, Jongkyoung; Zhang, Kelvin H. L.; Cho, Seungho; MacManus‐Driscoll, Judith L.
Abstract: Owing to the versatility in their chemical and physical properties, transition metal perovskite oxides have emerged as a new category of highly efficient photocatalysts for photoelectrochemical (PEC) water splitting. Here, to understand the underlying mechanism for the enhanced PEC water splitting in mixed perovskites, ideal epitaxial thin films of the BiFeO3 –SrTiO3 system are explored. The electronic structure and carrier dynamics are determined from both experiment and density‐functional theory calculations. The intrinsic phenomena are measured in this ideal system, contrasting to commonly studied polycrystalline solid solutions where extrinsic structural features obscure the intrinsic phenomena. It is determined that when SrTiO3 is added to BiFeO3 the conduction band minimum position is raised and an exponential tail of trap states from hybridized Ti 3d and Fe 3d orbitals emerges near the conduction band edge. The presence of these trap states strongly suppresses the fast electron–hole recombination and improves the photocurrent density in the visible‐light region, up to 16× at 0 V RHE compared to the pure end member compositions. This work provides a new design approach for optimizing the PEC performance in mixed perovksite oxides. Abstract : Epitaxial BiFeO3 –SrTiO3 thin films are investigated in order to understand the correlation between electronic structure and carrier dynamics in perovskite solid solution photoelectrodes. As well as shifting the conduction band edge up, an exponential tail of trap states emerges near the conduction band edge which suppresses the fast recombination of electrons and holes and strongly enhances the photocurrent density.